Characterizing Expression and Regulation of Gamma-Herpesviral Circular RNAs - Tagawa, Takanobu; Oh, Daniel; Santos, Jerico; Dremel, Sarah; Mahesh, Guruswamy; Uldrick, Thomas S.; Yarchoan, Robert; Kopardé, Vishal N.; Ziegelbauer, Joseph M. (Frontiers in Microbiology, 2021)
Multiple herpesviruses have been recently found to encode viral circular RNAs. Like cellular circular RNAs, these RNAs lack poly-A tails and their 5’ and 3’ ends have been joined, which confers protection from RNA exonucleases. We examined the expression patterns of circular RNAs from Kaposi’s sarcoma herpesvirus (KSHV) in various environments. We performed deep sequencing of circRNA-enriched total RNA from a KSHV-positive patient lymph node for comparison with previous circRNA-Seq results. We found that circvIRF4 is highly expressed in the KSHV-positive patient sample relative to both B cell lines and de novo infected primary vascular and lymphatic endothelial cells. Overall, this patient sample showed a viral circRNA expression pattern more similar to the pattern from B cell lines, but we also discovered new back-spliced junctions and additional viral circular RNAs in this patient sample. We validated some of these back-spliced junctions as circular RNAs with standard assays. Differential expression patterns of circular RNAs in different cell types led us to investigate what cellular factors might be influencing the ratio of viral linear mRNAs to circular RNAs. We found that repression of certain RNA-binding proteins shifted the balance between viral linear mRNAs and circular RNAs. Taken together, examining viral circular RNA expression patterns may become useful tools for discovering their functions, the regulators of their expression, and determining the stage and cell types of infection in humans.